Mengapa Aktivitas Fisik Tidak Cukup? General Self-Efficacy sebagai Penghubung Menuju Subjective Well-Being Mahasiswa - Khoirur Reza; Miftakhul Jannah (ANIMA Indonesian Psychological Journal, 2026)
Subjective well-being of university students is an important indicator in the context of higher education and is thought to be related to behavioral and cognitive factors. This study aims to examine the role of general self-efficacy as a mediator variable in the relationship between physical activity and subjective well-being in college students. This study involved 316 active college students who voluntarily participated and completed the study instrument completely to test a mediation model that places general self-efficacy as an intermediary variable in the relationship between physical activity and subjective well-being. The sample was determined using a purposive sampling technique with inclusion criteria tailored to the study objectives. Data were collected through a survey measuring: (1) physical activity using the International Physical Activity Questionnaire – Short Form (IPAQ-SF); (2) general self-efficacy using the General Self-Efficacy Scale for Higher Education; and (3) subjective well-being using the College Student Subjective Well-being Questionnaire. Data analysis used path modeling with a bootstrapping approach of 5,000 resamplings with 95% bias-corrected confidence intervals to estimate direct, indirect, and total effects more accurately. The analysis results showed that the direct effect of physical activity on subjective well-being was not significant (estimated coefficient = −1.094 × 10⁻⁷; p = .988). In contrast, physical activity had a significant effect on general self-efficacy (estimated coefficient = 2.993 × 10⁻⁵; p = .001), and general self-efficacy had a significant effect on subjective well-being (estimated coefficient = .647; p < .001). The indirect effect of physical activity on subjective well-being through general self-efficacy was proven to be significant (estimated coefficient = 1.937 × 10⁻⁵; p = .002), as was the total effect which showed statistical significance (estimated coefficient = 1.926 × 10⁻⁵; p = .042). The findings of this study indicate that the contribution of physical activity to student well-being primarily occurs through increased self-efficacy as an intermediary psychological mechanism.